KAJIAN PEMBUATAN ASAP CAIR TEMPURUNG KELAPA DENGAN PROSES PIROLISIS DAN DESTILASI DI SULAWESI UTARA - Balikan, Chikita M.; Tooy, Dedie; Wenur, Frans (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2021)
This research is aimed to study the pyrolysis and distillation processes of making liquid smoke from coconut shell related to the influence of time and number of raw materials to improve the efficiency of pyrolysis and distillation equipment. This study used an experimental method where the temperature in tube was set at 90° C and after 45 minutes it was maintained at 90° C and then lowered to 75° C. The observation period of the pyrolysis process was carried out every 30 minutes for 8 hours with 3 repetitions, while the distillation process was carried out every 45 minutes with 4 repetitions. The results of the pyrolysis process showed that the steam temperature and pyrolysis time had a relationship to the volume, yield, density and color of the liquid smoke. The average of temperature is 109.58°C gives average result of 6315 ml in volume, yield 21.60%, density 1.027 g/ml and the color is thick black. In the process of distillation, the temperature of steam in distillation affects the result. The temperature of 90°C of liquid smoke comes out quickly and a lot with a total volume of distillation 770 ml and a yellow-brown color. The temperature of 75°C of liquid smoke comes out slowly and the liquid smoke results slightly with a total volume of distillation 293 ml and a yellowish clear color. The color of liquid smoke using laboratory-scale distillation equipment is different from using a distillation tube tool, so it must be re-distilled to get a clearer color